2021
DOI: 10.1021/acs.est.1c00343
|View full text |Cite
|
Sign up to set email alerts
|

Passive Dosing of Petroleum and Essential Oil UVCBs—Whole Mixture Toxicity Testing at Controlled Exposure

Abstract: Petroleum products and essential oils are produced and used in large amounts and are categorized as "Substances of Unknown or Variable composition, Complex reaction products or Biological materials (UVCBs)." These UVCBs are notorious difficult-to-test substances, since they are complex mixtures of hydrophobic and volatile compounds. This study introduces two passive dosing (PD) approaches for whole UVCB toxicity testing:(1) headspace PD applies the UVCB and purified lipid oil as a donor to control exposure via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Unfortunately, testing the material which is left after DMSO extraction presents numerous challenges because the solvents that would need to be used are incompatible with in vitro testing. Alternative delivery of the “whole substance” can be achieved through passive dosing ( Hammershoj et al, 2020 ; Trac et al, 2021 ); however, the methods to deliver complex UVCBs in small volume in vitro testing conditions have not been established yet. Thus, additional work is needed to improve the relevance of in vitro test methods for use in regulatory decisions on UVCBs.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, testing the material which is left after DMSO extraction presents numerous challenges because the solvents that would need to be used are incompatible with in vitro testing. Alternative delivery of the “whole substance” can be achieved through passive dosing ( Hammershoj et al, 2020 ; Trac et al, 2021 ); however, the methods to deliver complex UVCBs in small volume in vitro testing conditions have not been established yet. Thus, additional work is needed to improve the relevance of in vitro test methods for use in regulatory decisions on UVCBs.…”
Section: Discussionmentioning
confidence: 99%
“…As UVCBs have multiple constituents of likely varying solubilities and percentage compositions, aquatic toxicity testing of UVCBs poses technical challenges for hydrophobic and/or volatile constituents. Thus, considerable studies in recent years have focused on developing improved toxicity testing methodologies for UVCBs, especially with respect to dosing of volatile, hydrophobic, and volatile and hydrophobic UVCBs, as well as analyzing the effect of sample preparation on bioavailability …”
Section: Hazard Assessment Of Uvcbsmentioning
confidence: 99%
“…Thus, considerable studies in recent years have focused on developing improved toxicity testing methodologies for UVCBs, especially with respect to dosing of volatile, hydrophobic, and volatile and hydrophobic UVCBs, 124−126 as well as analyzing the effect of sample preparation on bioavailability. 127 Overall, modeling toxicity and testing of UVCBs have mostly focused on petroleum substances, [124][125][126]128 solvents, 86,129 and chlorinated paraffins. 23,130−132 Future method development and toxicity evaluations of other UVCBs are warranted.…”
mentioning
confidence: 99%
“…Cedarwood oil was selected as a case study substance in the European Chemical Council (Cefic) long-range research initiative (LRI) ECO-42 project, 14 which has generated new data on biodegradation, 15 bioaccumulation potential for fish 13 and whole substance aquatic toxicity. 16 Characterisation data for the oil was provided by its distributor Givaudan UK Ltd and confirmed by gas-chromatography mass spectrometry (GC-MS). 13 Physical–chemical property data for the individual cedarwood oil constituents was taken from the literature or estimated using EPISuite (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Baseline toxicity and thus absence of excess toxicity was supported for cedarwood oil based on the whole UVCB toxicity tests that were conducted within the ECO-42 project. 16 For a general application of our framework for UVCB risk assessment, potential excess toxicity needs to be evaluated carefully and additional experiments might be necessary particularly with regards to potential endocrine disruptive effects or carcinogenicity. 29 The evaluation of decision criteria 1 and 2 indicated that no further characterization data was needed to perform the fatebased risk assessment of the unidentied constituents.…”
Section: Is the Risk Assessment Based On The Known Constituents Repre...mentioning
confidence: 99%